Desenvolvimento de banco de dados para seleção de porta-enxertos de citros em duas regiões do Estado de São Paulo visando à qualidade da fruta - Carmello, Fernanda Cristina (2021)
In the state of São Paulo, citrus growing has expanded throughout the state in areas that comprise the citrus belt, divided into five sectors which, in turn, are subdivided into 12 regions. This division took into account the characteristics of soil, climate and historical aspects related to the development of citrus production. Therefore, there are edaphoclimatic differences that influence the quality of the fruit. The rootstocks and their interaction with the scion variety also have an important influence on the quality of the fruit. This work sought to identify, among new varieties of canopy/rootstocks from Citrus breeding program of Sylvio Moreira Citriculture Center of Agronomic Institute (IAC), those that best meet the needs of citrus growers. In order to optimize the breeding programs, the objective was the development of a database and a software that use data of quality analyzes of the fruits, such as size, soluble solids content, juice and industrial yield, observing the variability and allowing the selection of best combinations of scions and rootstocks. The influence of 20 rootstocks on the physicochemical characteristics of Pera sweet orange trees, grafted as a scion cultivar, cultivated in the regions of Barretos (northern region of SP) and Gavião Peixoto (central region of SP) was evaluated. The variables studied were: total soluble solids (TSS), pH and total titratable acidity (TTA), juice yield and technological index in data accumulated in 2018 and 2019. The design used was a randomized block design, with 20 treatments (rootstocks). The results allowed us to conclude that there are statistically significant differences between locations, genotypes and there is an interaction between genotypes and environments. Thus, there are genotypes that are more suitable and more genetically stable for each of the regions. With the results of the technological index (IT) or industrial performance, the ideal genotype for Gavião Peixoto was citrandarin 26 and for Barretos, citrandarin 47. The database helped in the organization and visualization of the results of the evaluation of the quality of the fruits.